2022
DOI: 10.1021/acs.jafc.2c01672
|View full text |Cite
|
Sign up to set email alerts
|

Metabolome and Transcriptome Analysis Reveals the Transcriptional Regulatory Mechanism of Triterpenoid Saponin Biosynthesis in Soapberry (Sapindus mukorossi Gaertn.)

Abstract: Soapberry (Sapindus mukorossi Gaertn.) pericarps are rich in valuable bioactive triterpenoid saponins. However, the saponin content dynamics and the molecular regulatory network of saponin biosynthesis in soapberry pericarps remain largely unclear. Here, we performed combined metabolite profiling and transcriptome analysis to identify saponin accumulation kinetic patterns, investigate gene networks, and characterize key candidate genes and transcription factors (TFs) involved in saponin biosynthesis in soapber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 53 publications
0
20
0
Order By: Relevance
“…For sRNA sequencing, pericarp samples were collected from three trees. The details of these materials were described in our previous report ( Zhao et al., 2019 ; Xu et al., 2021b ; Xu et al., 2022 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For sRNA sequencing, pericarp samples were collected from three trees. The details of these materials were described in our previous report ( Zhao et al., 2019 ; Xu et al., 2021b ; Xu et al., 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…Then, module–trait associations were estimated by calculating the Pearson’s correlations between the MEs and the differentially accumulated saponin (DAS) content obtained from the pericarp materials from the same eight developmental stages determined previously by our group previously ( Table S1 ). Integrative analysis was also performed to determine correlations between miRNA MEs and mRNA MEs from the same samples ( Xu et al., 2022 ). Subsequently, we also performed Pearson’s correlation analysis to detect negatively associated miRNA–mRNA pairs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the biosynthesis mechanism of tea saponin in C. vietnamensis was analyzed, and the terpenoids synthesis pathway was studied (Figure S1). There were 49 genes putatively involved in sapogenin biosynthesis, and 54 saponins were identified by transcriptome and metabolome analysis [40]. In the previous study, we also identified some genes (such as SQS) related to the biosynthesis of tea saponins in C. vietnamensis [1].…”
Section: Candidate Structural Genes Involved In Theasaponins Pathway ...mentioning
confidence: 96%
“…Triterpenoids accumulation is controlled by multiple regulatory mechanisms, including transcriptional regulation and plant phytohormine signaling . The transcriptional level regulation has been considered a major aspect, and transcription factors (TFs) play vital roles in binding to promoters of triterpenoid-related genes to promote their transcription, which affects triterpenoid accumulation. , Although no studies have examined the regulation of triterpenoid biosynthesis by TFs in jujube, studies of the regulatory mechanisms in other species potentially provide some relevant insights. For example, GubHLH3 can positively regulate the key genes of triterpenoid biosynthesis in Glycyrrhiza uralensis …”
Section: Introductionmentioning
confidence: 99%